Online Contract Drafting Assistance For Small Medium Enterprise In The Gentan Raya, Baki, Sukoharjo Markets - Rina Arum Prastyanti; Faulinda Elynastiti (VSJ | Veteran Society : Jurnal Pengabdian Masyarakat, 2020)
The backgrounds of business actors in Pasar Raya Gentan are different. The majority of business actors have received the highest education from high school. The educational background of this business actor influences one's mindset and attitude in making decisions and facing problems. The lack of education resulted in a lack of knowledge of the significance of the Covenant. Business actors in the gentan market often use oral agreements that unconsciously lead to agreements. Preparation of Training Materials, At this stage, the team first makes a good and correct guidebook for writing agreements. Presentation of Contract Drafting and Review Business Contract Material, At this meeting the presenters provided socialization and understanding of the importance of contract drafting. In addition, participants were also given knowledge about the law of making contracts in business. Design (Skill Session), at this stage, participants are stimulated independently to be able to make a work agreement project which will later be applied in their field of work, Monitoring and Evaluation, after being deemed sufficient to master and understand the “Contract Drafting and Review Business Contract”, it is followed by monitoring and evaluating the success rate of contracting for participants, whether it has helped participants in implementing this training. The solution offered to partners is to provide assistance in contract design for business actors in Raya Gentan market. Contract drafting is an important element in a legal relationship. Contract drafting is a combination of two words, namely "contract" and "drafting". Literally, the word "contract" means promise, while "drafting" means designing / drafting. So contract drafting can be interpreted briefly as the design of an agreement. A complete understanding of contract drafting is very important for business actors.